Description of The Level of Independence of The Elderly in Fulfillment of Activity Daily Living (ADL) at UPTD Griya Werdha Jambangan Surabaya - Devi, Tiyas Marta; Dony Sulystiono; Alfi Maziyah; Shifaza, Fathimah (Global Ten Public Health and Nursing Journal, 2025)
Elderly is the term for the final stage of the process of obtaining the gift of longevity. Physical changes in the elderly will affect the level of independence. The independence of the elderly in the Activity of Daily Living (ADL) is defined as a person's independence in carrying out daily activities. Measuring the level of independence of respondents is done through observation techniques and interviews with respondents. The assessment instrument used in this study uses Barthel Index.The Barthel index consists of ten independent activities, namely eating, bathing, self-care, dressing, urinating, defecating, using the toilet, moving, mobility, going up and down stairs. Based on the results of the research that has been done, it is found that the majority of the elderly are included in the independent category of 71 people (41.3%). Data obtained that the majority of the elderly are most dependent on the activity of going down the stairs as many as 72 people (41.9%). Many elderly people need help in going up and down stairs caused by several factors, such as a decrease in the level of muscle strength due to increasing age. So that further action is needed to overcome the elderly who still have a low level of independence.